Perbandingan Efek Residu Kedua dan Ketiga Dari Aplikasi Vermikompos Pada Pertumbuhan dan Hasil Tanaman Selada Merah (Lactuca sativa L. var Crispa) - gabrilla fergiawan listianto (AGRONISMA, 2022)
Red lettuce (Lactuca sativa L.) has red leaves, wide, thin, bundles and curly, including one type of vegetable plant whose leaves are taken. The demand for lettuce production in Indonesia in 2017 increased but red lettuce production is still not optimal until now, so efforts are needed to increase red lettuce production by developing a cultivation system An alternative is cultivation without soil (hydroponics). The use of organic fertilizers is necessary because it is environmentally friendly so that a healthy agricultural system will produce healthy food. Vermicompost is a quality organic fertilizer. Vermicompost has both direct and indirect effects on plants, including improving the physical properties of the soil and providing the nutrients plants need. This study aims to determine the direct impact and residual effect of the application of vermicompost with red lettuce as an indicator in a soilless cultivation system. This research was conducted in a plastic house on Jl. MT. Haryono, Dinoyo, District Lowokwaru Malang with an altitude of ± 550 meters above sea level, air temperature ranging from 20-35oC, which was carried out from July to September 2021. The design used was a simple randomized block design (RAK) with 2 series (residue 2 and residue 3). In total there were 5 treatments plus 1 control using AB Mix nutrition. The results showed that the application of residue 2 and residue 3 of vermicompost significantly affected the growth and yield of red lettuce. In the second planting period (residual effect 3) the plants showed an increase in the total dry weight of the plant, the dry weight of economic value and the dry weight of the roots. Where the treatment with the highest increase was treatment V5 with an increase of 52.17% in the total dry weight variable, dry weight with economic value of 26.67% and root dry weight of 82.81%. Keywords: red lettuce, vermicompost residue, hydroponics.